Palkkatyöhön vai omistajayrittäjäksi : sosiokulttuurin heijasteet Jämsänkosken ammatillisten oppilaitosten opiskelijoiden työllistymispyrkimyksissä - Mäki, Juhani (1999)
The research sets out to examine the efforts of the students of the vocational colleges to obtain employment. The research is based on the fact that a human being and his or her behaviour are largely products of his or her culture. In this context the efforts to obtain employment mean the activity and the measures taken by the students to obtain employment either as an employee or as an owner-entrepreneur. The research is based on the theory of Kahn & Wiener on how people experience work and what is their attitude to it. The target group are the students of the vocational colleges in Jämsänkoski. A questionnaire-based survey was carried out at the colleges under the guidance of the teachers and 682 acceptable replies were received. The purpose of this research is to identify the connection of the cultural and social factors in the efforts of the students to obtain employment - to be an owner-entrepreneur or a wage worker, how the students value wage work and entrepreneurship and what are their attitudes to their future occupation. 1n addition the effectiveness of the education is researched in the choices of the students concerning employment and distinctive factors are searched between orientation to entrepreneurship and wage work. This research based on cultural and sociological factors indicates that 53 per cent of the students aimed at wage work i.e. try to get a job as employees and 47 per cent aimed at entrepreneurship i.e. most likely want to become owner-entrepreneurs. The college, the place of residence and the political distribution of the place of residence, the population and the forest industry tradition of the place of residence as well as the age and gender best explain the orientation to wage work. Excluding the two last mentioned predictors the factors mentioned above have a cultural reflection on the behaviour of the students. The relation between them is statistically very significant. The entrepreneurship of the parents and the college as cultural factors as well as the gender best explain the orientation to owner-entrepreneurship. The distinction is statistically very significant. The regression analysis revealed the willingness to solve problems, self-assurance and education. as the best predictors of the phenomenon. College, school class, age and gender best explain the effectiveness of the education as relates to entrepreneurship. The analysis of variance shows that success at school best explains the attribution and locus of internal control which are regarded as the virtues of entrepreneurship. According to the regression analysis, the same observation applies to respondents' age. The entrepreneurship background of the parents explains the appreciation of the entrepreneurs and in the regression analysis also independence and willingness to solve problems. Success at school best explains self-assurance as a result of the analysis of variance and in addition to the above also the income of the parents according to the regression analysis.